MORAL DETERIORATION OF ENGLISH SOCIETY IN VICTORIAN ERA AS SEEN IN OSCAR WILDE’S THE PICTURE OF DORIAN GRAY - Prisilia Hura (LINGUA LITERA : journal of english linguistics and literature, 2021)
Abstract This research aims to analyze the moral deterioration of English society in the Victorian Era in the novel The Picture of Dorian Gray by Oscar Wilde.Specifically, this research analyzes the reason for the moral deterioration of English society in the Victorian era and how moral deterioration affects British society. This study uses the theological theory by Ted Peter to analyze the selling soul to demons as the reason for moral deterioration, and the theory of Farhansyah to analyze hedonism as the effect of moral deterioration for British society in the Victorian era. This research finally underlined two major problems as the findings related to cause and effect in moral deterioration as seen on The Picture of Dorian Gray. The cause is selling souls to the demons. The effect of moral deterioration is hedonism. Related to hedonism, the writer only found two kinds of problems; ethical hedonism and aesthetic hedonism.